Adaptive fuzzy sliding mode control algorithm simulation for 2-DOF articulated robot. (2017) - Du, Feng; Sun, Ying; Li, Gongfa; Jiang, Guozhang; Kong, Jianyi; Jiang, Du; Li, Zhe
About articulated robot's control, chattering phenomenon existed in conventional sliding mode algorithm. Therefore a robotic adaptive fuzzy sliding mode control algorithm is also proposed. This kind of algorithm is designed as an adaptive single input and output fuzzy system to calculate the control gain. Meanwhile, the mathematical proof is carried out on system's stability and astringency by Lyapunov theory's adaptive law. The adaptive fuzzy sliding mode control is simulated in Simulink, the simulation results show that when the chattering becomes weaker, the function of the system is promoted. Fuzzy sliding mode controller can be changed and adjusted with the transformation of system's state. Steady-state convergence is constant, adaptive fuzzy sliding mode control algorithm still with a good robustness under the condition that articulated robot's parameters uncertain and external interference.